Challenges And Opportunities In Online Education In Sri Lanka During The Covid-19 Pandemic: Evidence From The University Of Kelaniya - Khashunika, J.A.L; Yatigammana, M.R.K.N; Lakmal K.G.P (CV. Inara, 2021)
The Sri Lankan government and the University Grant Commission (UGC) of Sri Lanka have encouraged every university and higher education institution to adopt online education methods in response to ongoing issues with the COVID-19 virus. This study examines the challenges and new opportunities in online education in Sri Lanka during the covid-19 epidemic. A qualitative approach was utilized to achieve the study's goals, and semi-structured interviews were conducted to gather data. The respondents were undergraduates and faculty members of the University of Kelaniya. Thematic analysis was performed to analyze the outcomes of the study. This research identified three major challenges and four significant opportunities in online education at the University of Kelaniya. The researchers also made several recommendations for an effective online education strategy based on the study's findings. The results provide essential guidance for modernizing conventional education and propose that Sri Lankan educational institutions reassess their learning methods.